Moderating Effect of Physical Exercise between the relation of Psychological Resilience and Negative Emotions of University Students in Iraq - Kessra Ahmed Fathy; Moyaed Abdul allah Jasim; Haider H. Jawad; Dhuha Salman Aljuboory; Abdul Razzaq Jabr Al Majidi; Yasmeen Ahmed Rashed; Ali Falah Mohamed Hassan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Negative emotions reduce the academic achievement of college students. Students in Iraq experience bad emotions due to the country's social conditions. The purpose of this project is to improve the mental health of Iraqi students through physical activity. This study aims to examine the moderating link between psychological resilience and negative emotions among university students in Iraq. This study collects quantitative data using a Likert scale questionnaire and a random sample technique; the participants were students from several Najaf universities. The findings of this study indicate that physical health plays a substantial moderating influence between psychological resilience and unpleasant emotions. According to the study, students' negative feelings can be lessened with health education and mental health literacy. These findings are unusual since this study's theoretical framework offers a substantial relationship to the existing research. Similar to the theoretical implications, this study has significant practical consequences that are crucial to consider while attempting to reduce the negative emotions component among Iraqi university students. The next directions of this research are important for addressing the literature gap in negative emotions.